Differences in Performance on Quality Measures for Thrombectomy‐Capable Stroke Centers Compared With Comprehensive Stroke Centers in 2019 to 2020 - David W. Baker; Stephen Schmaltz; Karen Kolbusz; Steven R. Messé; Edward C. Jauch; Lee H. Schwamm (Stroke: Vascular and Interventional Neurology, 2022)
Background Thrombectomy‐Capable Stroke Center (TSC) certification was created to improve timely access to mechanical thrombectomy (MT), where travel to a Comprehensive Stroke Center (CSC) would entail prolonged transport time. No study has evaluated the quality of MT and stroke care at TSCs compared with CSCs. Methods We compared performance for 3 MT measures for all TSCs and CSCs certified by The Joint Commission in 2019 and 2020: (1) time from arrival to skin puncture, (2) the percentage of patients who achieved Thrombolysis in Cerebral Infarction ≥2B perfusion, and (3) the proportion of patients with symptomatic hemorrhagic transformation following MT. Wilcoxon ranked‐sum tests and signed‐rank tests were used to compare TSCs and CSCs within years and changes in performance from 2019 to 2020. Results The median time from arrival to skin puncture was 75.8 minutes for CSCs compared with 106.1 minutes for TSCs in 2019 (P<0.001) and 74.8 minutes for CSCs compared with 91.7 minutes for TSCs in 2020 (P<0.001). For TSCs, the median time was 11.2 minutes lower in 2020 compared with 2019 (P<0.005). There were no differences in the median proportion of patients who had ThrombolysisinCerebralInfarction≥${\text{Thrombolysis in Cerebral Infarction}} \ge $2b perfusion achieved for CSCs compared with TSCs in 2019 (85.2% versus 84.3%, respectively; P=0.87) or 2020 (86.9% versus 88.6%, respectively; P=0.73). Rates of symptomatic hemorrhagic complications were similar. Conclusions Times from arrival to skin puncture were longer at TSCs compared with CSCs, although this difference narrowed significantly in 2020. This improvement and the similar rates of successful MT and complications at TSCs and CSCs support current recommendations to transport patients with suspected large‐vessel occlusion to a TSC if a CSC is >30 minutes longer transport time. However, routing decisions for suspected large‐vessel occlusion must be made at a local level based on the performance data for TSCs and CSCs.